2021
DOI: 10.1038/s41598-021-95209-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of NETosis markers and DAMPs have prognostic value in critically ill COVID-19 patients

Abstract: Coronavirus disease 19 (COVID-19) presents with disease severities of varying degree. In its most severe form, infection may lead to respiratory failure and multi-organ dysfunction. Here we study the levels and evolution of the damage associated molecular patterns (DAMPS) cell free DNA (cfDNA), extracellular histone H3 (H3) and neutrophil elastase (NE), and the immune modulators GAS6 and AXL in relation to clinical parameters, ICU scoring systems and mortality in patients (n = 100) with severe COVID-19. cfDNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 53 publications
8
73
0
1
Order By: Relevance
“…STROBE guidelines were followed for reporting. An initial description of this study could be found in Huckriede et al (2021). All 117 patients admitted to the central intensive care unit at Uppsala University hospital during the first wave of the pandemic in 2020, with suspected COVID-19 infection, were screened for inclusion.…”
Section: Collection Of Patient Samplesmentioning
confidence: 99%
“…STROBE guidelines were followed for reporting. An initial description of this study could be found in Huckriede et al (2021). All 117 patients admitted to the central intensive care unit at Uppsala University hospital during the first wave of the pandemic in 2020, with suspected COVID-19 infection, were screened for inclusion.…”
Section: Collection Of Patient Samplesmentioning
confidence: 99%
“…The unique inflammatory response exhibited by neutrophils whereby they release NETs as an effector mechanism is associated with poor clinical outcome in COVID-19 [34]. Several studies revealed the role of neutrophils in the pathology of the disease as levels of blood neutrophils and NETs released in COVID-19 patients were higher than those in a healthy cohort [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Two possible reasons may explain this discrepancy. First, besides plasma gp96, viral RNA and multiple other elevated DAMPs could also induce IL-6 expression, including cell-free DNA, extracellular histone H3, and neutrophil elastase, as well as the immune modulators GAS6 and AXL ( 11 , 25 ). In addition, in severe COVID-19, the levels of circulating mitochondrial DNA, S100A8/A9, and high mobility group box 1 were also significantly increased and were correlated with inferior clinical outcomes ( 11 , 26 ).…”
Section: Discussionmentioning
confidence: 99%